2011
DOI: 10.12973/ejmste/75197
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of an Instrument to Measure Greek Primary Education Teachers’ Biology Teaching Self-efficacy Beliefs

Abstract: The self-efficacy beliefs of in-service elementary school teachers in Greece were examined in an attempt to evaluate their biology teaching skills. For this purpose, we constructed a valid and reliable instrument consisting of a Likert-type questionnaire that was distributed to the target population and to which 202 teachers responded. Results revealed Greek primary education teachers have, in general, moderate to high biology teaching selfefficacy beliefs (BioTSEB), whereas those that had not attended any bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…In Greece, the relevant research is rather limited, focusing mainly on modifications of the instrument to measure teachers' self-efficacy beliefs in biology and environmental sciences teaching (Malandrakis, 2017;Mavrikaki & Athanasiou, 2011); however, no relevant research has been detected using the MTEBI to examine Greek pre-service teachers' efficacy beliefs in mathematics teaching. By adapting both the STEBI-B and MTEBI instruments into the Greek language and by examining their psychometric properties, this study contributes to the existing literature and aims to address this gap.…”
Section: Introductionmentioning
confidence: 99%
“…In Greece, the relevant research is rather limited, focusing mainly on modifications of the instrument to measure teachers' self-efficacy beliefs in biology and environmental sciences teaching (Malandrakis, 2017;Mavrikaki & Athanasiou, 2011); however, no relevant research has been detected using the MTEBI to examine Greek pre-service teachers' efficacy beliefs in mathematics teaching. By adapting both the STEBI-B and MTEBI instruments into the Greek language and by examining their psychometric properties, this study contributes to the existing literature and aims to address this gap.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with those of Nadelson and Nadelson (2010), who found that teachers need PD on teaching evolution, not in general, but in a specific and focused on teaching content. Primary education teachers who had not attended any biology courses during their academic studies, they showed lower self-esteem about teaching biology subjects (Mavrikaki and Athanasiou 2011).…”
Section: Discussionmentioning
confidence: 96%
“…■ emotional attitude (e.g., Benz, 2008;Cavallo et al, 2002;Downing et al, 1997;; ■ interest and enjoyment (e.g., Benz, 2010;Downing et al, 1997;Alao & Guthrie, 1999; ■ enthusiasm (e.g., ; and ■ perceived self-efficacy (e.g., Mavrikaki & Athanasiou, 2011;Buss;.…”
Section: Measurementmentioning
confidence: 99%